2014
DOI: 10.1140/epjb/e2014-50311-2
|View full text |Cite
|
Sign up to set email alerts
|

Coercivity reduction in a two-dimensional array of nano-particles

Abstract: We report on theoretical investigation of the magnetization reversal in two-dimensional arrays of ferromagnetic nano-particles with parameters of cobalt. The system was optimized for achieving the lowest coercivity in an array of particles located in the nodes of triangular, hexagonal and square grids. Based on the numerical solution of the non-stochastic Landau-Lifshitz-Gilbert equation we show that each particle distribution type is characterized with a proper optimal distance, allowing to lower the coercivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…They found that coercivity increases with arrays disorder. (c) Using the Landau-Lifshitz-Gilbert approach, Morales-Meza et al studied the magnetization reversal in a two-dimensional array of MNPs [28]. They showed that coercivity is reduced even if the particle position in the array is random.…”
Section: Introductionmentioning
confidence: 99%
“…They found that coercivity increases with arrays disorder. (c) Using the Landau-Lifshitz-Gilbert approach, Morales-Meza et al studied the magnetization reversal in a two-dimensional array of MNPs [28]. They showed that coercivity is reduced even if the particle position in the array is random.…”
Section: Introductionmentioning
confidence: 99%